OC-045 Efficacy & safety of dose adjustment & delayed response to ustekinumab in moderate–severe crohn's disease patients: results from im-uniti maintenance study. (17th June 2017) - Sands, B; Gasink, C; Jacobstein, D; Gao, L; Johanns, J; Szapary, P; Colombel, J; Targan, S; Ghosh, S; Sandborn, W
Abstract : Introduction: Ustekinumab (UST) induced/maintained clinical response (CR) and remission (CRM) in mod-severe Crohn's disease (CD) as shown in 2 induction (UNITI-1 and 2) and 1 maintenance (IM-UNITI) RCT, placebo (PBO) controlled phIII trials. We evaluated UST efficacy in 2 more grps in IM-UNITI: pts undergoing dose adjustment after loss of response (LOR) and pts without a CR to IV UST during induction and had an additional SC dose. Method: Pts achieving CR after single dose IV induction randomised to SC PBO, UST 90 mg/q12w or q8w. Pts meeting LOR criteria (i.e. CDAI ≥220 and a≥100 point ←from baseline maintenance CDAI score, between wks 8–32 of IM-UNITI trial) underwent a single dose adjustment as follows: PBO→q8w, q12w→q8w, and q8w→q8w (no dose adjustment) and assessed for CR (≥100 point ↓in CDAI) and CRM (CDAI <150) 16 wks later. Separately, UST pts not in CR 8 wks after IV dose given SC UST 90 mg and if CR 8 wks later stayed on q8w. Results: 51 (39%), 29 (23%), and 28 (22%) pts in PBO, q12w and q8w grps, respectively, had dose adjustment after meeting LOR criteria. We observed CRM and CR in 39% and 71% of pts adjusting PBO→q8w (situation similar to drug holiday), 41%–55% in q12w→q8w grp and 32%–46% in q8w→q8w grp assessed 16 wks later respectively (Table 1). Median CDAI change after adjustment was −121, –141 and −78.5 in PBO→q8w, q12w→q8w and q8w→q8w grs, respectively. UST 467 pts not in response after IV dose, 50.5%–28.9% had CR and CRM 8 wks after 1 extra UST dose (90 mg SC). Of 251 of these pts continued dosing at wk 8 of maintenance, 68.1% had CR and 50.2% CRM at wk 44. No ←or changes in AEs seen among dose adjustment pts. Conclusion: Pts meeting LOR criteria, dose adjustment from UST 90 mg/q12w to q8w had some additional clinical benefit vs pts remaining on UST 90 mg/q8w. Initial induction non-responders pts can benefit from continued treatment with at least 1 SC UST dose 8 wks after IV induction. Disclosure of Interest: B. Sands: None Declared, C. Gasink Conflict with: Janssen R and D, LLC, D. Jacobstein Conflict with: Janssen R and D, LLC, L. Gao Conflict with: Janssen R and D, LLC, J. Johanns Conflict with: Janssen R and D, LLC, P. Szapary Conflict with: Janssen R and D, LLC, J. Colombel: None Declared, S. Targan: None Declared, S. Ghosh: None Declared, W. Sandborn: None Declared